Environmental and biophysical controls of evapotranspiration from Seasonally Dry Tropical Forests (Caatinga) in the Brazilian Semiarid - Marques, Thiago Valentim (2020)
Seasonally dry tropical forests are among the most important biomes regarding regional and global hydrological and carbon fluxes. Thus, the objective of this study was to evaluate the seasonal and interannual variability of evapotranspiration (ET) and its biophysical control and characteristics (surface conductance—Gs; decoupling coefficient—Ω; ratio between actual evapotranspiration and equilibrium evapotranspiration—ET/ETeq) in a preserved Caatinga Biome environment during two dry years in the Northeast Brazil region. A study on this subject with this level of detail in this biome is unprecedent. Measurements were carried out using an eddy covariance system during the period from 1st January 2014 to 31st December 2015. The lowest ET values were observed in the dry season of both experiment years (0.3 and 0.2 mm day−1) as a consequence of poor water availability, which favored partial stomatal closure and reduced Gs values (0.22 and 0.13 mm s−1). The opposite occurred in the wet season, when ET (2.6 and 1.7 mm day−1) and Gs (3.74 and 2.13 mm s−1) means reached higher values. Regarding annual values, differences between total annual rainfall in both years is the most probable cause for the differences observed in annual ET values. In 2014, annual ET was of 473.3 mm while in 2015 it was 283.4 mm, which incurred in an overall decrease in Gs, Ω and ET/ETeq values. Leaf senescence and extremely low Gs values during the dry season suggest that the trees of the Caatinga Biome are more resilient regarding the use of water and are avoiding water stress caused under low water availability